The Correlated Factors of Mandatory Social Reporting by Islamic Banks in Indonesia - Dodik Siswantoro (Institute for Research and Community Empowerment (LPPM TAZKIA), 2012)
Objective – Islamic Banking is closely related to the real sector. Then, its operation should reflect the real sector which is expected to contribute to the sustainable economic growth. Nevertheless, Islamic banks are still benchmarking the price of their products (profit sharing and sales) on interest rate. This is as an implication of the implementation of the dual banking system. Moreover, the small portion of Islamic banking compared to the total national banks causes the competitiveness of Islamic banking product in terms of pricing has a high correlation with the interest rate of conventional counterpart. This phenomenon indicates the need to find.Method – This research employed library research method since this paper relies on secondary data by thoroughly reviewing the most relevant literature. The paper attempt to propose a pricing indicator which is based on the real sector activities as the root of Islamic banking operations.Result – Theoretically, this indicator can reflect the real rate of return of every industry sector. In addition, it can help Bank Indonesia to monitor the real sector performance and analyze the possible gap between real sector activities and financial sector. Furthermore, when the benchmark of real rate of real sector return is available, the return index of Islamic banking reflecting the profit sharing performance of the whole Islamic banking industry can be formulated. This concept is different with other indexes which are corresponding to the price of financial assets.Conclusion – In general, return index of real sector as a reference for Islamic banking product pricing is expected to define the way of non-interest return analysis, to calculate the non-interest return of selected sectors that becomes the focus of analysis using Cash Recovery Rates (CRR), forming an index of industry by sector in the second stage, by doing a certain weighting of those companies, to analyze the relationship between macro factors and CRR by sector and to forecast. Modeling the Demand for Family and General Takaful in Malaysia (A Comparative Study): ARDL Approach to CointegrationObjective- Nowadays, numerous studies focus on the determinant of the demand for takaful, either family or general takaful in Malaysia. In this respect, these studies employ economic and socio-demographic variables to examine the determinants of takaful. They found that income, interest rates, financial development, pensions, stocks, price of insurance, life expectancy, dependency ratio, education, and age have positive on determinants of takaful. However, previous tudies have found that inflation, savings, and unemployment rate have negative relationship with the determinant of takaful in Malaysia. This study attempts to examine the determinants of the demand for family takaful and general takaful for comparative study in Malaysia for the period of 1988 to 2010. It employs economic and socio-demographic variables to measure these determinants.Methods-Using time series data, this study applies the Autoregressive Distributive Lag (ARDL) approach to cointegration to examine the determinants of the demand for family takaful and general takaful in the short and long run.Result-The findings indicate that the economic and socio-demographic variables such as income, and education have positive relationship with the demand for family takaful in the short run, but not in the long run.Conclusion-Meanwhile, it also indicates that income and education have no relationship with demand for general takaful in Malaysia in the short run and long run. It indicates that if there is an increase in income, people tend to buy more family takaful of STMB. At the same time, the educated people already aware of the takaful products, they may necessarily purchase family takaful than life insurance. Objective – The objective of this paper is to analyze the profit distribution method applied in Islamic banks in Indonesia and to propose better method in order to improve sharia risk compliance.Methods – Employing a descriptive quantitative method and literature review. This paper evaluate weaknesses of the current profit distribution method and proposes daily revenue index to solve the problems arising from using current method which is unfairness between bank and customers.Results – By the two current profit distribution methods which use monthly revenue index calculated only at the end of the month, there are potential injustices occur. Therefore, instead of using monthly index, daily index is proposed. There are two steps in calculating profit distribution by using daily revenue index: (1) Accumulating Source of Fund (SoF), Reserve Requirement (RR), and Source of Fund after Reserve Requirement (SoFaRR), and (2) Determining Average Financing (AF), Revenue Index (RI), Cost Index (CI), Revenue Sharing Index (RSI), and Profit Sharing Index (PSI).Conclusion - Daily revenue index will solve the unfairness problems arise from current profit distribution method applied in Islamic banks. Daily revenue index is also applicable if Islamic banks apply profit and loss sharing instead of revenue sharing. Objective – This study will try to describe inclusive asset building (further abbreviated as IAB ) concept which proposed by Michael Sherreden and it’s implementation as the main agenda of ZIS institutions activities. Anti-poverty proposals from various parties include government agencies, private and public, generally focusing on income subsidy policy to encourage public demand over the minimum edge (borderline poverty) of live well.Method - Library research is applied since this paper relies on secondary data by thoroughly reviewing the most relevant literature. This will be elaborated starting from the introduction of mechanisms and IAB programs in the main activities of ZIS institutions. In addition, several prerequisites adjustments and strengthening either in terms of institutional, organizational capacity and management needs to be conducted by the ZIS institutions so that this study will achieve as expected.Results -.Combination of income support with the asset accumulation such as subsidise saving for the poor will be more long-term. Which is expected to help out the poor from socio-economic alienation. Through the implementation of this concept, ZIS institutions have a chance to heighten the leverage of their role in poverty alleviation.Conclution – All resources, either internal and external that have been built by LAZ during these days, is a valuable capital to initiate the paradigm shift. Also, the benefits of institutional characteristics and closely relationship with the clients (mustahik) could be additional notes. Objective – Islamic finance has been established as an alternative to the conventional banking system which is made up component not permitted under Shariah. Tawarruq is one of the Islamic finance products which commonly used in Islamic banks. This research assesses two important areas which include the principle of Tawarruq in Fiqh perspective and the practical aspect of such principle in Islamic banks in Malaysia.Method – The method used for this research is comparative analysis.Result – This research begins to explore the different views of the proponent and opponents toward the legality of Tawarruq in Fiqh . Instead of considering the basic condition of the valid sale, the other aspect has to be pondered by the contemporary scholars to render Tawarruq is valid sale according to Shariah. The legality of Tawarruq has been debate by some scholars. Due to that, there are different resolution and rulings from Islamic countries on legality of of Tawarruq . In the practical aspect, Tawarruq has been used in Malaysia by Bursa Malaysia Suq Al Sila' as a trading platform and it uses Crude Palm Oil (CPO) as the commodity in Tawarruq transaction. While, in the Middle East, it uses London Metal Exchange (LME) in dealing with commodity transaction through Tawarruq principle.Conclusion – Based on the legal argument on the permissibility of Tawarruq , it can be summarized that Tawarruq is permissible but subject to certain condition. Provided that genuine Tawarruq is permissible than organized Tawarruq in Tawarruq transaction.Keywords: Tawarruq, Murabahah Objective – This research aimed to analyze zakat calculation practices from online providers. There are some differences in the calculation method, for example different treatment in zakatable deduction, types of income and zakat for business.Methods - Twenty-three zakat online calculators are analyzed and then grouped into a main category. A simulation model is employed by inputting several common assumptions.Results - The results showed that generally three zakat calculator become main providers and differences are still occur.Conclusion – This research showed that the calculation of zakat should be simpler, standardized, and may not cause double zakat counting for profession-zakat. Government should intervene to provide a single zakat calculation method that must be refereed by all zakat institutions and link it to tax system.Keywords: Zakat, accounting, calculation, online Objective – The objective of this paper is to provide a discussion whether Islamic securities enjoy larger demands than conventional securities. This paper also investigate whether regulator could effectively take a role in materializing demands for Islamic securities and whether regulator declaration is more convincing than sharia compliance declaration by another institution.Methods - We employ differences in differences (DID) regression to see the immediate, medium, and long term market response to this announcement. We also estimate cumulative abnormal returns by employing the standard market model for the robustness test.Results - We find that market reacts to sharia compliance declaration by regulator in the long-run, hence potential demands are realized and the Islamic securities will enjoy greater market power. We also provide evidence that Islamic investors are not too strict in screening Islamic securities and are willing to accept different opinions regarding sharia compliance.Conclusion - This finding could explain why Islamic finance is still growing rapidly even though there are critiques in the genuineness of sharia compliance of the current Islamic financial products/services.Keywords: Regulator, Islamic securities, sharia compliance, demand, investor confidence 7-2-2012Objective- The main objective of this study is to estimate the Willingness to Pay of the Muslim households to contribute cash waqf as a strategy towards wealth management in Sri Lanka. Waqf is holding or confinement which is emphasised in Islam as ibadah as it can distribute the wealth among the Muslim society and would help to develop the Islamic vision of brotherhood.Method- Contingent valuation method is used to estimate the Willingness to Pay of Muslim households to improve socio-economic status of the low income people through waqf wealth management in Sri Lanka. This study is developed based on Random Utility Theory.Result- This paper identifies the appropriate methods to estimate the willingness to pay of Muslim households in Sri Lanka for waqf (awqaf is plural) institutions. Such evaluations are crucial for the Islamic financial system to function effectively in order to achieve the dignified objectives of socio-economic justice through proper distribution of wealth.Conclusion-This paper presents a conceptual model of waqf institutions which would be useful for further empirical research in this area. The findings are not only appropriate and applicable to Sri Lanka but also to other Muslim and non-Muslim countries. This is a unique contribution to the Islamic economic literature. The knowledge obtained from this study hopes to propose cash waqf to manage the wealth in order to improve the socio-economic status of low income people in Sri Lanka.Tujuan - Tujuan utama dari penelitian ini adalah untuk memperkirakan Kemauan Membayar rumah tangga Muslim untuk berkontribusi wakaf tunai sebagai strategi menuju pengelolaan kekayaan di Sri Lanka. Wakaf secara bahasa menahan (harta) yang ditekankan dalam Islam sebagai ibadah karena dapat mendistribusikan kekayaan di antara masyarakat Muslim dan akan membantu untuk mengembangkan visi Islam yaitu persaudaraan.Metode - Metode penilaian Kontingensi digunakan untuk memperkirakan Kesediaan membayar rumah tangga Muslim dalam meningkatkan status sosial - ekonomi masyarakat berpenghasilan rendah melalui pengelolaan kekayaan wakaf di Sri Lanka. Penelitian ini dikembangkan berdasarkan Teori Utilitas Acak.Hasil - Paper ini mengidentifikasi metode yang tepat untuk memperkirakan kemauan membayar rumah tangga Muslim di Sri Lanka untuk wakaf lembaga. Evaluasi tersebut sangat penting untuksistem keuangan Islam yang berfungsi secara efektif dalam rangka mencapai tujuan yang bermartabat keadilan sosial - ekonomi melalui distribusi kekayaan yang tepat.Kesimpulan - Paper ini menyajikan model konseptual lembaga wakaf yang akan berguna untuk penelitian empiris lebih lanjut di daerah ini. Temuan ini tidak hanya tepat dan berlaku untuk Sri Lanka, tetapi juga ke negara-negara Muslim dan non -Muslim lainnya. Ini adalah kontribusi yang unik untuk literatur ekonomi Islam. Pengetahuan yang diperoleh dari studi ini adalah mengharapkan agar wakaf tunai diusulkan untuk mengelola kekayaan dalam rangka meningkatkan status sosial - ekonomi masyarakat berpenghasilan rendah di Sri Lanka.Keywords: Awqaf, Contingent Valuation Method, Utility Theory, Willingness to Pay, Welfare Changes Objective – The purpose of this research is to analyze correlated factors related to social reporting by Islamic banks in Indonesia. According to the accounting standard in Indonesia, Islamic banks are legally required to report on social aspects. Social reporting is regulated in Indonesia under the accounting standard for Islamic Financial Institutions No. 1. Islamic banks must present social reporting in a standardized format.Methods-The present research methodology analyzes financial reports from Islamic banks between 2006 and 2011. It also analyzes correlated factors based on supporting variables.Results- This research reveals that asset, debt, net income and temporary investment have the highest correlation to social reports by Islamic banks in Indonesia. In addition, older, full-fledged Islamic banks have different characteristics compared to new, full-fledged banks in terms of charity, fines, non-halal funds, and other fund correlations.Conclusion- This research shows that the bigger the bank the bigger social reporting given. In addition, better zakat management is shown by new Islamic bank full fledged group as adaptations in the standard.Keywords: social, report, accounting, Islamic bank